Ekosistem SDM dan Inovasi Ekonomi Digital di Indonesia - Salistia, Faisal; Riyanto, Riyanto; Junaedi, Dedi; Amalia, Rika Sri (Sci-tech Journal, 2023)
The purpose of this study is to analyze the efforts to develop the HR and innovation ecosystem in the digital economy. The research method used is a qualitative analysis method with a litteature study approach. In general, the condition of human resources and digital economy innovation (startup) in Indonesia is still minimal. The lack of human resources makes national digital business actors "nudge" each other to compete for human resources, until finally "damaging" the wage standards of digital human resources themselves. An easier digital industry will certainly be easier to pay dearly for each competent individual. Meanwhile, small industries, which actually train their human resources more from the start, have to "bite their fingers". The portrait of the availability of human resources in the field is still lacking. Therefore, synergies and cointegration between various stakeholders need to be carried out. As a regulator and facilitator, the government must take the initiative to take strategic steps with other stakeholders to contribute positively to human resource development and innovation in the digital economy in Indonesia. One of them is through the implementation of the curriculum from vocational, vocational, and tertiary institutions and accelerated professional/skill certification to overcome the scarcity of human resources. As well as HR planning to support the digital era of entrepreneurship Keywords: HRD ecosystem, digital economy innovation, Indonesia